EMERGING ARTIFICIAL INTELLIGENCE, ART AND PEDAGOGY: EXPLORING DISCUSSIONS OF CREATIVE ALGORITHMS AND MACHINES FOR ART EDUCATION - Nicholas Leonard (Digital Culture & Education, 2021)
The continued development and emergence of creative machines and computational creativity provokes certain questions that audit ontological and epistemological assumptions. Creative artificial intelligence challenges computer scientists, digital artists, and art educators to clarify or reconceptualize their notions of cognition and creativity. The article starts by addressing the increase in AI algorithms in both daily life and formal education settings to begin highlighting the shared investment across domains. The focus is then narrowed down to highlight creative machines and digital artmaking. By exploring the statements and artworks from computer scientists and digital artists, correlations to art education pedagogical approaches are then constructed. This will then lead into a recognition for a need to challenge and examine the ontological and epistemological assumptions present in art education. Finally, a new material theoretical framework for digital art education pedagogy is proposed to reorient discussions to ask new questions regarding increasingly creative machines and the experiences and education of students in the visual arts